Students’ Ability In Giving Definition as Prime Minister in Speaking for Debate Class at Muhammadiyah Univeristy of Bengkulu - Rizky Amelia Putri (Teaching English and Language Learning English Journal, 2022)
The definition in the aspect of debate assessment is a very important aspect in starting a debate, it is used for the boundaries of a motion so that the issues to be debated can be more focused. Therefore, it is necessary to have a clear definition of each motion so that the public can understand the scope of the debate. The purpose of this research is to know and describe Students' Ability in Giving Definition as Prime Minister in Speaking for Debate at Muhammadiyah University Of Bengkulu. The research design of this study used a qualitative descriptive method. The instruments used were observation checklists and interviews. The subjects of this research were fourth semester students as Prime Ministers who take speaking for debate courses in the English Education Program for the 2020/2021 academic year. The results of this study showed that the ability of students to provide a definition as a prime minister in the high category. This study indicates that English students in the fourth semester at Muhammadiyah University of Bengkulu to have a better understanding on how to give a good definition especially in the aspect of not be self proving as prime minister. For further researchers, it is suggested that could be use to find out the students argument quality especially in definition aspect. Keywords : Speaking, Debate, Definition